ERRORS IN USING ENGLISH AS CLASSROOM LANGUAGE COMMITTED BY THE ICT TEACHER OF SMP NEGERI 2 SEMARANG - Huyi Intan Sari (EduLite: Journal of English Education, Literature and Culture, 2016)
This article aims to discuss the problems faced by the ICT teacher of SMP Negeri 2 Semarang in using English as classroom language. The International Standard School project is a new education policy in Indonesia that was enacted with a main goal to prepare the students for global competition. This policy is both an effort to internationalize schools in Indonesia and a part of the national education decentralization reform. The title International Standard School, SBI in Bahasa, is given as an accreditation status to schools that have completed the required standards. This accredited status requires the school to carry out teaching and learning process all in English. This applies to all subjects including ICT. This article is based on the observation on the teaching and learning process in ICT class at SMP Negeri 2 Semarang as one of famous International Standard Schools in Semarang. The observation has resulted in general problems which is elaborated in the teaching documents four aspects of language mastery; fluency, pronunciation, grammar, and vocabulary.